2014
DOI: 10.5731/pdajpst.2014.00999
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Against a Bacterial Endotoxin Masking Effect in Biologic Drug Products by Limulus Amebocyte Lysate Detection

Abstract: Bacterial endotoxin is a Gram-negative bacterial cell wall component that is harmful to humans at threshold concentrations, and it is not expected to be in aseptically-produced pharmaceutical medicines. It has been suggested that endotoxin cannot be detected over time in certain biopharmaceutical drug product formulations containing citrate, phosphate, and polysorbate components via an unknown masking mechanism. We have generated and present data here that indicate that endotoxin can be recovered in a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…LPS in native endotoxin is imbedded in cell wall fragments and may be protected from the dispersing effects of chelating buffers and surfactants and is therefore probably not prone to masking effects. Hence, it is argued that the observed masking effects would only represent an artefact emerging from faulty experimental design – as claimed in recent studies performed by Bolden et al 1415…”
mentioning
confidence: 84%
“…LPS in native endotoxin is imbedded in cell wall fragments and may be protected from the dispersing effects of chelating buffers and surfactants and is therefore probably not prone to masking effects. Hence, it is argued that the observed masking effects would only represent an artefact emerging from faulty experimental design – as claimed in recent studies performed by Bolden et al 1415…”
mentioning
confidence: 84%
“…There is a discussion on the difference in LER effects between purified LPS and naturally occurring endotoxin (NOE). NOE is relatively resistant to LER [5,6,9,10]. Structures of NOE are affected by the environment of the growth of the bacteria.…”
Section: (4)mentioning
confidence: 99%
“…The interfering factors test is based on the confirmation of acceptable recovery (50%-200%) in a diluted sample. Samples in LER studies were usually diluted with water for the BET, and the diluted samples were confirmed to overcome interference of the sample by the interfering factors test [5][6][7][8][9][10]. This indicated that the diluted samples were not inhibitory to the activation of LAL, and that endotoxin activity in the diluted samples should be detected by the BET if there was still activity of the spiked endotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…According to the "3Rs principle" for laboratory animals (Franco & Olsson, 2013), which represents reduction, refinement, and replacement, there is a need to find alternative approaches to test pyrogens. Several international groups have recently developed new in vitro pyrogen testing methods (Daneshian, Guenther, Wendel, Hartung, & Aulock, 2006;Fennrich et al, 2016). However, variation among monocyte donors means that this test requires monocytes from four different individuals, and as acquiring fresh human mononuclear cells can be a problem for many laboratories, this method is not very easy to implement (Burger-Kentischer, Abele, Finkelmeier, Wiesmüller, & Rupp, 2010;Nakagawa, Maeda, & Murai, 2002;Timm, Hansen, Moesby, & Christensen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, variation among monocyte donors means that this test requires monocytes from four different individuals, and as acquiring fresh human mononuclear cells can be a problem for many laboratories, this method is not very easy to implement (Burger-Kentischer, Abele, Finkelmeier, Wiesmüller, & Rupp, 2010;Nakagawa, Maeda, & Murai, 2002;Timm, Hansen, Moesby, & Christensen, 2006). Several international groups have recently developed new in vitro pyrogen testing methods (Daneshian, Guenther, Wendel, Hartung, & Aulock, 2006;Fennrich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%